Lilypond Music-Notation Software in the Digital-Humanities Toolbox. - Cashner, Andrew A. (DHQ: Digital Humanities Quarterly, 2024)
The music-notation software Lilypond generates high-quality music typography from a plain-text input format; almost every aspect of the program can be customized and programmed, and the system lends itself well to automation and batch processing. Lilypond offers a minimal computing alternative to bloated, costly, and hegemonic graphical programs. Like many free software tools, however, Lilypond still exacts a cost in time and training needed to overcome an unwieldly interface and adapt the tool for scholarly purposes. The author developed a system called lirio that enabled the production of two critical editions and a monograph in Lilypond (integrated with LaTeX). The system provides a new semantic-markup interface to Lilypond that enables scholars to think about typography separately from musical content; a range of expanded Lilypond functionality including incipit staves, mensural coloration brackets, and editorial annotations; and a stricter input format that makes Lilypond files easier to maintain. The author also developed the prototype ly2mei compiler to demonstrate how Lilypond files can be converted to MEI-XML, overcoming a major limitation in Lilypond's export abilities. The article argues that scholars will be best served by a simple, consistent, meaningful interface in a format that can be shared and converted. An extension of Lilypond like lirio demonstrates the considerable potential of this tool for enterprising and patient scholars whose needs are not met by other tools. Lilypond provides a case study for how to make open-source, free-license tools work for our own needs as digital humanists. Lilypond music-notation software as a case study: how to make open-source tools work for us.